Resveratrol’s bibliometric and visual analysis from 2014 to 2023 - Wei, Haoyue; Fang, Guowei; Song, Weina; Cao, Hongye; Dong, Ruizhe; Huang, Yanqin (Frontiers in Plant Science, 2024)
Resveratrol (RSV) is a natural polyphenolic compound derived from a variety of plants that possesses a wide range of biological activities, including antioxidant, anti-inflammatory, antitumor, antibacterial, antiviral, anti-aging, anti-radiation damage, anti-apoptosis, immune modulation, regulation of glucolipid metabolism, inhibition of lipid deposition, and anti-neuro. It is therefore considered a promising drug with the potential to treat a wide range of diseases. In this study, using Web of Science Core Collection (WoSCC) and CiteSpace bibliometric tool, VOSviewer quantitatively visualized the number of countries, number of authors, number of institutions, number of publications, keywords, and references of 16,934 resveratrol-related papers from 2014-2023 for quantitative and qualitative analysis. The results showed that an average of 1693.4 papers were published per year, with a general upward trend. China had the most publications with 5877. China Medical University was the institution with the largest number of publications and the highest number of citations in the field. The research team was mainly led by Prof. Richard Tristan, and the journal with the highest number of published papers was Molecular. Dietary polyphenols, oxidative stress, and antioxidant and anti-inflammatory effects are the most frequently cited articles. Oxidative stress, apoptosis, expression, and other keywords play an important role in connecting other branches of the field. RSV has a promising application in the fields of medicine and health care. How to modify its structure to obtain RSV derivatives with better bioactivity and bioavailability is the future research challenge for researchers.